Highly substantive water-resistant pigment and method for its preparation

The pigment preparation method using a three-layer composite structure design solves the problems of high colorfastness, water resistance, and mineral-like texture in pigments, achieving superhydrophobicity and high rubbing fastness, while maintaining color stability during long-term use.

CN120924086BActive Publication Date: 2026-11-06BEIJING JIYUAN AESTHETIC CULTURE & ART TRAINING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511119670.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-11
Publication Date
2026-11-06
Estimated Expiration
2045-08-11

AI Technical Summary

Technical Problem

Existing technologies struggle to simultaneously achieve high colorfastness, water resistance, and a mineral-like appearance in pigments. Furthermore, traditional methods suffer from issues such as chemical compatibility conflicts between the hydrophobic layer and the color-fixing layer, insufficient functionalization of the mineral-like crystal structure, and inadequate long-term weather resistance.

Method used

The three-layer composite structure design includes pigment core pretreatment, hydrophobic layer construction, aminosilane introduction and fixation layer polycondensation. The hydrophobic layer and the fixation layer are synergistically linked by chemical bonds to form a superhydrophobic and abrasion-resistant pigment.

Benefits of technology

It achieves superhydrophobicity with a contact angle ≥150°, color fastness to dry/wet rubbing ≥4.5, and the core crystal structure restores the feel of natural minerals. After QUV aging for 400h, the color difference △E* ≤6.5.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120924086B_ABST
    Figure CN120924086B_ABST
Patent Text Reader

Abstract

This invention discloses a high-fixation waterproof pigment and its preparation method, belonging to the field of functional pigment development. The pigment consists of a three-layer composite structure: the pigment core is a synthetic silicate mineral (formed by solid-phase reaction sintering of ceramic glaze, mineral powder and rare earth elements), the hydrophobic group modification layer is formed by chemical grafting of a fluorinated silane coupling agent (such as perfluoroalkyl silane) on the core surface, and the color-fixing crosslinking layer is constructed by polycondensation of aminosilane and polycarboxylic acid polymer to build a three-dimensional network. The preparation method includes: (1) pretreatment and activation of the pigment core; (2) modification with fluorinated silane to form a hydrophobic layer; (3) introduction of aminosilane; (4) polycondensation of polycarboxylic acid polymer to build a color-fixing layer; (5) post-treatment. The obtained pigment has ultra-high waterproofness, dry / wet friction resistance ≥4.5 grade and excellent weather resistance, and is suitable for mural restoration and high-end coatings, solving the technical problems of the difficulty in synergistic waterproofness and color-fixing properties of traditional pigments and the limited imitation of mineral hues.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional pigment development, and particularly relates to a high-fixation waterproof pigment and its preparation method. Background Technology

[0002] Pigments, as color carriers, are widely used in coatings, inks, and cultural relic restoration, especially in the restoration of ancient murals, where they must simultaneously meet the requirements of high colorfastness (resistance to friction and washing) and water resistance (resistance to erosion in humid environments). However, traditional pigments, such as organic pigment powders, fade easily, while inorganic pigments (such as iron oxide), although stable, have limited hues; ceramic glazes, although rich in hues, lack the texture of natural mineral crystals due to their amorphous glassy phase structure and have weak adhesion to the substrate, with a wet rubbing fastness of only 1-2. Existing technologies struggle to simultaneously meet the triple requirements of water resistance, colorfastness, and a mineral-like appearance.

[0003] Current methods for improving pigment performance have significant drawbacks. Waterproofing modification: While grafting with fluorine / silicon compounds can increase the contact angle (approximately 130°), the hydrophobic layer has weak adhesion to the core and is easily detached due to friction. Color fixation enhancement: Although coating with carboxyl polymers improves adhesion, the introduction of hydrophilic groups leads to a sharp drop in waterproofing. Mineral imitation: Artificial mineral pigments can simulate the hues of natural minerals by sintering mineral powder mixed with glazes, but the surface functionalization problem remains unresolved, and waterproofing and color fixation are not optimized.

[0004] Existing technologies have failed to overcome three major barriers: ① the chemical compatibility conflict between the hydrophobic layer and the color-fixing layer; ② the functional modification that mimics the mineral crystal structure; and ③ the guarantee of long-term weather resistance. Especially in the field of mural restoration, it is necessary to simultaneously restore the texture of mineral crystals, resist environmental erosion, and ensure high color fastness. This invention proposes a three-layer composite structure through a synergistic design of "core mineralization + surface functionalization," providing an integrated solution for high-end applications. Summary of the Invention

[0005] To address the challenges of restoring the texture of mineral crystals, resisting environmental erosion, and ensuring high color fastness.

[0006] To address the above problems, the present invention provides the following technical solution:

[0007] A high-fixation, waterproof pigment, characterized by comprising the following steps:

[0008] S1: Pigment core pretreatment activation: suspension pH 3.5–5.5, stirred at 50–70℃ for 30–90 min;

[0009] S2: Hydrophobic layer construction: Add fluorinated silanol solution (fluorinated silane: alcohol = 1:2–1:10wt), react at 75–85℃ for 2–5h;

[0010] S3: Introduction of aminosilane: Add 2–8% aminosilane by weight of pigment core and react at 70–80℃ for 1–3 h;

[0011] S4: Condensation of the color-fixing layer: Add 3–15% by weight of the pigment core to the polycarboxylic acid polymer, pH 4.0–5.5, condensation at 75–85℃ for 3–6 hours;

[0012] S5: Post-treatment: Wash until neutral and free of ion residue, then vacuum dry at 60–100℃ for 8–16 hours.

[0013] Preferably, the pigment core sintering process involves heating to 400°C for 40 minutes and holding for 30 minutes, then heating to 1230°C for 60 minutes and cooling in the furnace, followed by water quenching at 400°C after removal from the furnace.

[0014] Preferably, the pigment is used in mural restoration, architectural coatings, or waterproof textiles.

[0015] Preferably, the pigment has the following properties: contact angle ≥150°, dry rubbing color fastness ≥4.5 grade, and wet rubbing color fastness ≥4 grade.

[0016] Preferably, the pigment has a color difference ΔE* ≤ 6.5 after QUV aging for 400h.

[0017] The effects and advantages of the high-fixation waterproof pigment and its preparation method of the present invention are as follows:

[0018] 1. This patent achieves a breakthrough in triple performance: the hydrophobic layer (containing fluorinated silane) and the color-fixing layer (aminosilane / polycarboxyl polymer network) are bridged by chemical bonds to achieve superhydrophobicity with a contact angle ≥150°, high color fixation with dry / wet friction resistance ≥4.5, and the core crystal structure restores the natural mineral feel (particle size controllable from 50nm to 2μm).

[0019] 2. This patent has excellent structural stability. The hydrophobic layer is grafted with the core by covalent bonds, and the color-fixing layer is formed by in-situ polycondensation to form a cross-linked network. The two layers are bridged by chemical bonds. After QUV aging for 400 hours, the color difference ΔE* ≤ 6.5.

[0020] 3. This patented process has strong universality and is applicable to inorganic / organic pigment cores, reducing raw material costs.

[0021] 4. This patent enhances the richness of hues, expanding to over a hundred kinds of natural mineral hues, thus solving the problem of insufficient color gamut in mural restoration. Attached Figure Description

[0022] Figure 1 This is a flowchart of a high-fixation waterproof pigment and its preparation method according to the present invention. Detailed Implementation

[0023] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0024] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitation, an element defined by the phrase "comprising..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0025] Example 1

[0026] refer to Figure 1 This embodiment provides a high-fixity waterproof pigment and its preparation method, which imitates malachite green mineral color, including the following implementation details:

[0027] Experimental objective:

[0028] A high-fixation waterproof pigment and its preparation method are disclosed. The synergistic effect of the three-layer structure with cobalt blue glaze as the core, perfluorosilane (F13) as the hydrophobic layer and polyacrylic acid (PAA) as the color-fixing layer is verified. The waterproof performance (contact angle), color fastness (dry / wet rubbing) and weather resistance (QUV aging) are tested in detail.

[0029] Experimental materials:

[0030] 60g cobalt blue ceramic glaze (CoAl2O4), 50g porcelain clay (kaolinite), 40g flux (borax), 2g tridecafluorooctyltriethoxysilane (F13), 6g γ-aminopropyltriethoxysilane (KH550), 8g polyacrylic acid (PAA), 20g anhydrous ethanol, 600ml deionized water.

[0031] Experimental equipment:

[0032] Thermostatic mechanically stirred reactor (with nitrogen protection), precision pH meter, high-speed centrifuge (≥8000rpm), vacuum drying oven, contact angle meter (DSA100), color fastness tester for rubbing (GB / T 3920), QUV accelerated aging chamber (ISO 4892-3).

[0033] Experimental steps:

[0034] S1: Core pretreatment and activation: Take 100g of sintered and crushed cobalt blue-based core powder (particle size 1μm), add 600ml of deionized water, and ultrasonically disperse for 30 minutes; adjust the pH to 4.5 with 10% acetic acid solution, and mechanically stir (500rpm) in a 70℃ constant temperature water bath for 60 minutes.

[0035] S2: Hydrophobic layer construction: Dissolve 2g F13 in 20g anhydrous ethanol and slowly add it dropwise to the activated suspension (complete the addition within 1 hour); heat to 80℃ and stir under nitrogen protection for 4 hours.

[0036] S3: Introducing aminosilane, add 6g KH550 to the reaction system and stir at 80℃ for 2 hours;

[0037] S4: Polycondensation of the color-fixing layer, add 8g PAA (prepared as a 10% aqueous solution), adjust the pH to 5.0 with 10% triethylamine, and perform polycondensation reaction at 80℃ for 5 hours;

[0038] S5: Post-treatment: Cool the reaction solution to room temperature and centrifuge (8000 rpm, 10 min); wash the precipitate 4 times with deionized water (500 ml each time) and 2 times with anhydrous ethanol (200 ml each time); dry the filter cake under vacuum at 80℃ for 12 hours and pass it through a 300-mesh sieve to obtain the finished product.

[0039] Example 1 Test Results:

[0040] Example 1: A high-fixation waterproof pigment and its preparation method. The water contact angle reaches 152°, mainly attributed to the grafting of the tridecafluorooctyl chain of F13 onto the core surface via Si-O covalent bonds, forming a low surface energy monolayer. Furthermore, the KH550 / PAA condensation polymer constructs nanoscale protrusions on the hydrophobic layer surface, forming a lotus leaf-like micro-nano composite structure, causing water droplets to roll off in a spherical shape. Dry rubbing color fastness reaches grade 4-5. The carboxyl groups (-COOH) of polyacrylic acid (PAA) and the amino groups (-NH2) of aminosilane (KH550) condense to form an amide crosslinking network (-CO-NH-), "encapsulating and locking" the pigment particles. Wet rubbing color fastness reaches grade 4. The hydrophobic layer blocks water molecule penetration, and the siloxane skeleton (Si-O-Si) in the crosslinking layer exhibits strong hydrolytic stability, resisting water molecule swelling and damage. After 400 hours of QUV aging, the ΔE* is 5.5. The F13 CF bond has high bond energy, absorbing UV radiation and protecting the core chromophore (Co).2+ It is protected from photodegradation; at the same time, the cross-linked network fills the defects on the core surface, blocks the oxygen / moisture penetration path, and delays the oxidation reaction.

[0041] Example 2

[0042] This embodiment provides a high-fixity, waterproof pigment and its preparation method, which imitates cinnabar mineral color, including the following implementation details:

[0043] Experimental objective:

[0044] A high-fixation waterproof pigment and its preparation method are disclosed. The synergistic effect of using ceramic glaze red as the core, perfluorosilane (F13) as the hydrophobic layer and acrylic-maleic anhydride copolymer (AA-MA) as the fixing layer is verified. The effect of dispersant PEG on improving wet rubbing fastness and weather resistance is investigated.

[0045] Experimental materials:

[0046] 60g ceramic glaze (Fe2O3-based), 50g feldspar, 40g flux (borax), 2g tridecafluorooctyltriethoxysilane (F13), 6g γ-aminopropyltriethoxysilane (KH550), 6g acrylic acid-maleic anhydride copolymer (AA-MA, Mw~8000Da, AA:MA=70:30), 1g polyethylene glycol (PEG, Mw2000), 20g anhydrous ethanol, 600ml deionized water.

[0047] Experimental steps:

[0048] S1: Core pretreatment and activation: Take 100g of sintered and crushed red base core powder (particle size 1.5μm), add 600ml of deionized water, and ultrasonically disperse for 30 minutes; adjust the pH to 4.5 with 10% acetic acid solution, and mechanically stir (500rpm) in a 70℃ constant temperature water bath for 60 minutes;

[0049] S2: Hydrophobic layer construction: Dissolve 2g F13 in 20g anhydrous ethanol and slowly add it dropwise to the activated suspension (complete the addition within 1 hour); heat to 80℃ and stir under nitrogen protection for 4 hours.

[0050] S3: Introducing aminosilane and dispersant, add 6g KH550 and 1g PEG to the reaction system, and maintain stirring at 80℃ for 2 hours;

[0051] S4: For the color-fixing layer polycondensation, add 6g of AA-MA (prepared as a 10% aqueous solution), adjust the pH to 4.8 with 10% triethylamine, and perform polycondensation reaction at 80℃ for 4 hours;

[0052] S5: Post-treatment: Cool the reaction solution to room temperature and centrifuge (8000 rpm, 10 min); wash the precipitate 4 times with deionized water (500 ml each time) and 2 times with anhydrous ethanol (200 ml each time); dry the filter cake under vacuum at 80℃ for 12 hours and pass it through a 300-mesh sieve to obtain the finished product.

[0053] Example 2 Test Results:

[0054] Example 2: A high-fixation waterproof pigment and its preparation method. The water contact angle reaches 149°, mainly attributed to the dynamic balance mechanism of hydrophobic / hydrophilic groups. The perfluoroalkyl chain of fluorosilane (F13) forms a low surface energy monolayer on the core surface of the pigment. Meanwhile, the hydrophobic alkyl chains generated after the hydrolysis of maleic anhydride units in the fixing layer acrylic-maleic anhydride copolymer (AA-MA) synergistically counteract the influence of hydrophilic carboxyl groups, maintaining a high contact angle for water droplets. The dry rubbing fastness reaches grade 4-5 due to the physical anchoring effect of the dense cross-linked network. The dicarboxyl groups of AA-MA condense with the primary amino groups of aminosilane (KH550) to form high-density amide bonds, strongly locking the pigment particles within the three-dimensional network. The key to improving wet rubbing color fastness to grade 4-5 lies in enhanced hydrolytic stability. The cyclic anhydride structure in AA-MA hydrolyzes to form β-carboxylamide bonds, which exhibit better water resistance than linear ester bonds. Furthermore, the dispersant PEG (polyethylene glycol) fills the gaps in the cross-linked network, blocking the penetration pathway of water molecules. The water wash fastness reaching grade 5 is attributed to the synergistic color-fixing mechanism of ionic bonds. The high carboxyl density of AA-MA and the CaO content of the mural lime substrate... 2+ Stable ionic crosslinking is formed, resisting the emulsification effect of soap solution. The QUV aging color difference ΔE* is as low as 3.7 due to the antioxidant effect of PEG. Its ether bonds preferentially oxidize to generate peroxide free radicals (·OOR), which consume environmental oxygen and block the photocatalytic chain reaction of Fe2O3 core. At the same time, the saturated alkane chains in the AA-MA copolymer slow down the photooxidative chain breakage of the main chain, so that the pigment hue still maintains >95% of the original color saturation after 400h accelerated aging.

[0055] Example 3

[0056] This embodiment provides a high-fixity waterproof pigment and its preparation method, which imitates the mineral color of lapis lazuli, including the following implementation details:

[0057] Experimental objective:

[0058] A high-fixation waterproof pigment and its preparation method are disclosed. The synergistic effect of the hydrophobic layer modified with long-chain fluorosilane (F17) and the polyaspartic acid sodium (PASP) color-fixing crosslinking layer is verified. The feasibility of extreme waterproof performance (contact angle > 160°) and its impact on abrasion resistance are tested.

[0059] Experimental materials:

[0060] 60g of ceramic glaze aquamarine (Co3O4-Al2O3-SiO2-based), 50g of feldspar, 40g of flux (borax), 3g of heptadecafluorodecyltrimethoxysilane (F17), 5g of N-β(aminoethyl)-γ-aminopropyltrimethoxysilane (KH792), 12g of sodium polyaspartate (PASP, Mw~3000Da), 25g of isopropanol, and 600ml of deionized water.

[0061] Experimental steps:

[0062] S1: Core pretreatment activation: Take 100g of sintered and crushed aquamarine core powder (particle size 800nm), add 600ml of deionized water, and ultrasonically disperse for 30 minutes; adjust the pH to 4.5 with 10% acetic acid solution, and mechanically stir (500rpm) in a 70℃ constant temperature water bath for 60 minutes.

[0063] S2: Hydrophobic layer construction: Dissolve 3g F17 in 25g isopropanol and slowly add it dropwise over 1.5 hours; heat to 85℃ and stir under nitrogen protection for 3 hours.

[0064] S3: Introducing aminosilane, add 5g KH792 (diamino structure), maintain 85℃ and stir for 1.5 hours;

[0065] S4: Polycondensation of the color-fixing layer, add 12g PASP (prepared as a 12% aqueous solution), adjust the pH to 5.2 with 10% triethylamine, and perform polycondensation reaction at 85℃ for 3.5 hours;

[0066] S5: Post-treatment: Cool the reaction solution to room temperature and centrifuge (8000 rpm, 10 min); wash the precipitate 4 times with deionized water (500 ml each time) and 2 times with anhydrous ethanol (200 ml each time); dry the filter cake under vacuum at 80℃ for 12 hours and pass it through a 300-mesh sieve to obtain the finished product.

[0067] Example 3 Test Results:

[0068] Example 3 describes a high-fixity waterproof pigment and its preparation method. The water contact angle is 165°. The heptadecyl chain, derived from F17, fully extends during a high-temperature reaction at 85°C, forming a low-defect-density monolayer on the core surface. Micron-scale papillary structures are induced by isopropanol solvent, which, together with nano-scale siloxane aggregates, construct a superhydrophobic surface. Dry friction resistance of 4-5 is attributed to the high mechanical strength of the β-amide bond in PASP. The secondary amide structure (-NH-CO-) in its main chain has a higher bond energy than the carboxyl group in PAA, and the dual amino groups of KH792 provide dual crosslinking points, forming a rigid network. Wet friction resistance of 4 is attributed to the hydrolysis resistance of the β-amide bond. Its cyclic structure has a higher hydrolysis barrier than the linear amide bond, and the low molecular weight of PASP (3000 Da) results in smaller network pores, hindering water molecule penetration. The QUV aging color difference ΔE* is 6.2, slightly higher than in Example 2. This is mainly because PASP has weak UV absorption, its β-amide bonds have no strong absorption in the 290–400 nm wavelength range, and its low molecular weight results in insufficient shielding of the core (Co3O4) by the crosslinking network. 2+ Oxidized to Co 3+ However, it is still within an acceptable range (ΔE* < 6.5).

[0069] Comparative Example 1

[0070] A traditional high-fixation waterproof pigment and its preparation method are provided. Only a hydrophobic layer containing fluorosilane (F13) is constructed, without a color-fixing crosslinking layer. This method is suitable for the development of functional pigments and includes the following implementation details:

[0071] Experimental objective:

[0072] A traditional high-fixation waterproof pigment and its preparation method are presented. The influence of the lack of a color-fixing crosslinking layer on the pigment performance is verified, and the necessity of the color-fixing layer in the three-layer structure is clarified.

[0073] Experimental materials:

[0074] 60g cobalt blue ceramic glaze (CoAl2O4), 50g porcelain clay (kaolinite), 40g flux (borax), 2g tridecafluorooctyltriethoxysilane (F13), 20g anhydrous ethanol, 600ml deionized water.

[0075] Experimental steps:

[0076] S1: Core pretreatment activation: Take 100g of sintered cobalt blue core powder (particle size 1μm), add 600ml of water, adjust the pH to 4.5, and stir at 70℃ for 60min.

[0077] S2: Hydrophobic layer construction, F13 ethanol solution (2g + 20g ethanol) was added dropwise, and the reaction was carried out at 80℃ for 4h (N2 protection);

[0078] S3: Post-treatment: Cool the reaction solution to room temperature and centrifuge (8000 rpm, 10 min); wash the precipitate 4 times with deionized water (500 ml each time) and 2 times with anhydrous ethanol (200 ml each time); dry the filter cake under vacuum at 80℃ for 12 hours and pass it through a 300-mesh sieve to obtain the finished product.

[0079] Comparative Example 1 Test Results:

[0080] Comparative Example 1 provides a traditional high-fixation waterproof pigment and its preparation method. The water contact angle is 130°. Due to the lack of a fixing layer, F13 molecules are randomly stacked on the core surface, and the fluoroalkyl chains cannot form a dense monolayer, resulting in increased surface energy and insufficient nano-roughness, causing water droplets to spread out. The dry rubbing color fastness reaches grade 1-2. The hydrophobic layer (F13) is only connected to the pigment core through silanol condensation, resulting in weak adhesion. During rubbing, the hydrophobic layer easily peels off from the core, leading to a high pigment particle shedding rate. The wet rubbing color fastness reaches grade 1. The pigment surface lacks hydrophilic groups (such as -COOH, -NH2), preventing the formation of hydrogen or ionic bonds with the substrate. Water acts as a lubricant, accelerating pigment peeling from the substrate. After 400 hours of QUV aging, ΔE* is 12.3. The lack of a fixing crosslinking layer hinders the shielding effect of the cobalt blue core (CoAl2O4). 2+ It is oxidized to Co under ultraviolet radiation. 3+ Meanwhile, defects on the core surface accelerate oxygen / moisture penetration, causing lattice expansion and pulverization. The combined effects of photo-oxidation and mechanical degradation cause the color difference to far exceed the threshold.

[0081] Example 1 provides a high-fixation, waterproof pigment and its preparation method. This example achieves excellent comprehensive performance through a three-layer structure design of cobalt blue glaze core, F13 hydrophobic layer, and PAA color-fixing layer. The water contact angle reaches 152°, attributed to the formation of a low surface energy monolayer by the tridecafluorooctyl chain of F13, combined with the micro / nano composite structure constructed by KH550 / PAA condensation polymer, achieving a lotus leaf-like hydrophobic effect. Dry rubbing color fastness reaches grade 4-5, thanks to the amide crosslinking network formed by the condensation of PAA carboxyl groups and KH550 amino groups, effectively locking the pigment particles; wet rubbing color fastness is grade 4, due to the hydrophobic layer blocking water penetration and the hydrolytic stability of the siloxane skeleton. After 400 hours of QUV aging, the color difference ΔE* is 5.5, because the CF bond of F13 absorbs ultraviolet radiation, protecting the core chromophore (Co). 2+ Meanwhile, the cross-linked network blocks the oxygen / moisture permeation pathway, delaying the oxidation reaction.

[0082] Example 2 uses Fe2O3-based bright red glaze as the core, combined with an F13 hydrophobic layer and an AA-MA color-fixing layer, and introduces a PEG dispersant to optimize performance. The water contact angle reaches 149° due to the synergistic effect of the F13 fluorocarbon chain and the AA-MA hydrophobic alkyl chain, balancing the influence of hydrophilic carboxyl groups. Dry rubbing color fastness is grade 4-5, originating from the high-density amide bond network formed by the AA-MA dicarboxyl groups and the KH550 amino group; wet rubbing color fastness is improved to grade 4-5, thanks to the water resistance of the AA-MA β-carboxyl amide bond and the PEG blocking water molecule penetration. Washing color fastness reaches grade 5, due to the interaction between the AA-MA carboxyl groups and the lime-based Ca... 2+ Ionic crosslinking is formed. The QUV aging color difference ΔE* is only 3.7, thanks to the antioxidant effect of PEG consuming environmental oxygen, and the AA-MA saturated alkane chain slowing down photo-oxidative chain scission, maintaining color saturation above 95%.

[0083] Example 3 uses a Co3O4-Al2O3-SiO2-based aquamarine glaze core, achieving extreme water resistance with a long-chain F17 hydrophobic layer and a PASP color-fixing layer. The water contact angle reaches 165° because the F17 heptadecafluorodecyl chain forms a low-defect monolayer at high temperatures, combined with an isopropanol-induced micron-sized papillary structure, constructing a superhydrophobic surface. Dry rubbing color fastness is grade 4-5, thanks to the high mechanical strength of the PASP β-amide bonds and the KH792 double amino crosslinking; wet rubbing fastness is grade 4, due to the hydrolysis-resistant properties of the β-amide bonds and the dense network of low-molecular-weight PASP that impedes water molecules. The QUV aging color difference ΔE is 6.2, slightly high because the PASP has weak UV absorption and insufficient shielding of the core (Co3O4), resulting in some Co... 2+ Oxidized to Co 3+ However, it still meets the standard of ΔE < 6.5.

[0084] Comparative Example 1, containing only an F13 hydrophobic layer and lacking a color-fixing crosslinking layer, exhibits significantly degraded performance. The water contact angle is 130°, due to the increased surface energy caused by the disordered stacking of F13, resulting in insufficient nano-roughness. Dry rubbing color fastness is only grade 1-2, due to the weak bond between the hydrophobic layer and the core, making it prone to peeling during rubbing; wet rubbing fastness is grade 1, due to the lack of hydrophilic groups to bond with the substrate, allowing moisture to accelerate pigment detachment. The QUV aging color difference ΔE* is as high as 12.3, due to the absence of a color-fixing layer for shielding, and the core Co... 2+ Oxidized to Co 3+ Furthermore, surface defects cause lattice expansion and pulverization, and the superposition of photo-oxidation and mechanical degradation leads to color difference far exceeding the threshold.

[0085] Those skilled in the art will recognize that the modules and algorithm steps of the various examples described in conjunction with the embodiments disclosed herein can be implemented in electronic hardware or a combination of computer software and electronic hardware. Whether these functions are implemented in hardware or software depends on the specific application and design constraints of the technical solution. Those skilled in the art can use different methods to implement the described functions for each specific application, but such implementation should not be considered beyond the scope of this application.

[0086] In addition, the functional modules in the various embodiments of this application can be integrated into one processing module, or each module can exist physically separately, or two or more modules can be integrated into one module.

[0087] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of protection of the claims.

[0088] In conclusion, the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included in the protection of the present invention.

Claims

1. A high-fixation, waterproof pigment, characterized in that, This pigment has a three-layer composite structure, consisting of a pigment core (synthetic silicate mineral, formed by solid-state reaction sintering of ceramic glaze, mineral powder, and rare earth elements, with a particle size of 50nm–2μm), a hydrophobic group modification layer (a covalent graft layer formed by chemical bonding between a fluorinated silane coupling agent and the pigment core surface), and a color-fixing crosslinking layer (a three-dimensional crosslinking network layer formed by the condensation reaction of an aminosilane compound and a polycarboxyl polymer). The hydrophobic group modification layer and the color-fixing crosslinking layer are bridged by chemical bonds. The fluorinated silane coupling agent is at least one of perfluoroalkyl ethyltriethoxysilane, tridecafluorooctyltriethoxysilane, and heptadecafluorodecyltrimethoxysilane. The aminosilane compound is at least one of γ-aminopropyltriethoxysilane and N-β(aminoethyl)-γ-aminopropyltrimethoxysilane; The polycarboxylated polymer is at least one of polyacrylic acid, acrylic acid-maleic anhydride copolymer, and sodium polyaspartate.

2. The high-fixation waterproof pigment as described in claim 1, characterized in that, The ceramic glaze is selected from at least one of cobalt blue, praseodymium yellow, scarlet, and golden brown, the mineral powder is feldspar or kaolin, and the rare earth element is cerium oxide or lanthanum oxide.

3. The high-fixation waterproof pigment as described in claim 1, characterized in that, The pigment properties meet the following requirements: contact angle ≥150°, dry rubbing color fastness ≥4.5 grade, and wet rubbing color fastness ≥4 grade.

4. The high-fixation waterproof pigment as described in claim 1, characterized in that, The pigment has a color difference ΔE* ≤ 6.5 after QUV aging for 400h.

5. The application of a high-fixation waterproof pigment as described in any one of claims 1-4 in mural restoration, architectural coatings, or waterproof textiles.

6. A method for preparing a high-fixation waterproof pigment according to any one of claims 1-4, characterized in that, Includes the following steps: S1: Pigment core pretreatment activation: suspension pH 3.5–5.5, stirred at 50–70℃ for 30–90 min; S2: Hydrophobic layer construction: Add a fluorinated silanol solution dropwise, wherein the ratio of fluorinated silane to alcohol is 1:2–1:10 wt, and react at 75–85℃ for 2–5 h; S3: Introduction of aminosilane: Add 2–8% aminosilane by weight of pigment core and react at 70–80℃ for 1–3 hours; S4: Condensation of the color-fixing layer: Add 3–15% of the pigment core mass of the polycarboxylic acid polymer, condense at pH 4.0–5.5, 75–85℃ for 3–6 hours; S5: Post-treatment: Wash until neutral and free of ion residue, then vacuum dry at 60–100℃ for 8–16 hours.

7. The method for preparing a high-fixation waterproof pigment as described in claim 6, characterized in that, The pigment core sintering process involves heating to 400°C for 40 minutes and holding for 30 minutes, then heating to 1230°C for 60 minutes and cooling in the furnace, followed by water quenching at 400°C after removal from the furnace.

Citation Information

Patent Citations

  • Preparation method of environment tolerance super-hydrophobic mineral substance pigment

    CN110079139A

  • Coating material for multifunctional superphobic layers

    US20020123561A1